Learning Transported : Augmented, Virtual and Mixed Reality for All Classrooms - Donally, Jaime (Book collections on Project MUSE., 2018)
"Teachers nationwide are adopting immersive technology- devices and software that provide augmented, virtual and mixed reality experiences- to enable students to go on virtual field trips, manipulate 3D objects and augment the world around them. Immersive technology resources can be far less costly than many believe, but there are issues school districts should resolve before making purchases and implementing this technology. Learning Transported provides practical insights and classroom examples to help educators plan and establish goals so that their investment in immersive technology benefits the greatest number of students."--Proporcionat per l'editor.